DFT study on the mechanism of the Diels–Alder reactions leading to bicyclo[4.2.0]octenones. (March 2016) - Haghdadi, Mina; Moradi, Ali; Bosra, Hassan Ghasemnejad
The regioselectivity and mechanism of the Diels–Alder reaction (DA) between 2-substituted cyclobut-2-enones and some electron-rich 1, 3-butadiene derivatives, were studied using density functional theory (DFT). Four possible reaction pathways, which are related to the formation of bicyclo[4.2.0]oct-3-en-7-ones, were investigated using natural bond orbital analysis, geometrical parameter and energy analysis and also DFT-based reactivity indices. The energy and bond order analyses show that the larger activation energy prevents the formation of meta products. Therefore ortho products are preferred and the process follows an asynchronous concerted mechanism with a polar nature via DA cycloaddition. Moreover, high regio- and stereoselectivity have been seen in the DA reaction of 2-cyanocyclobut-2-enone.